Kajian Kualitas Yogurt Menggunakan Starter Komersil (Lactobacillus Bulgaricus) - Yurliasni Yurliasni (Universitas Andalas, 2007)
The objective of this experiment was to study the quality of yoghurt produced by using a commercial starter culture of lactobacillus bulgaricus. Raw milk which was prepared by mixing 12 % powder milk into distilled water was placed into 12 Erlenmeyer glasses of 250 ml each. The glasses were divided into 3 groups of 4 glasses each as replications. Each group of milk in the glasses was added 3 different levels of 5; 7.5 and 10 % of commercial starter of L. bulgaricus. After well mixing, the Erlenmeyer's were incubated in an oven with temperature of 40 - 45oC for 5-6 hours to produce yoghurt. The yoghurt products were chemically analyzed for determination of pH, lactic acid, and fat and crude protein content. Data were statistically analyzed for variance analysis in a completely randomized design. Results showed that there were no significant efects of using different levels of starter culture. The quality of yoghurt products in term of pH, acidity, protein and content satisfied the quality standard.